2019
DOI: 10.1111/cpf.12585
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between supine and standing bioimpedance spectroscopy devices and dual‐energy X‐ray absorptiometry for body composition determination

Abstract: Background Research comparing bioimpedance spectroscopy (BIS) to dual-energy X-ray absorptiometry (DXA) is limited, especially with newer BIS devices that take measures in a standing position instead of the traditional supine position.Purpose The purpose of this study was to compare a standing BIS device (BIS STA ) and a supine BIS device (BIS SUP ) to DXA for measuring body fat percentage (BF%), fat mass (FM) and fat-free mass (FFM) in a cohort of male and female subjects displaying a wide range of ages and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…Notably, USG levels in all participants were ≤1.020. Body composition was measured by bioelectrical impedance spectroscopy (BIS) using methods previously described (SOZO Device, ImpediMed, Limited, Brisbane, Qld, Australia) [14]. This method has been shown to produce test-retest intraclass correlation coefficients (ICC) >0.990 for whole body fat mass, fat-free mass, and percent body fat in 29 men and women with comparable results to dual-energy X-ray absorptiometry in 95 men and women [14].…”
Section: Body Composition and Hydration Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, USG levels in all participants were ≤1.020. Body composition was measured by bioelectrical impedance spectroscopy (BIS) using methods previously described (SOZO Device, ImpediMed, Limited, Brisbane, Qld, Australia) [14]. This method has been shown to produce test-retest intraclass correlation coefficients (ICC) >0.990 for whole body fat mass, fat-free mass, and percent body fat in 29 men and women with comparable results to dual-energy X-ray absorptiometry in 95 men and women [14].…”
Section: Body Composition and Hydration Testingmentioning
confidence: 99%
“…Body composition was measured by bioelectrical impedance spectroscopy (BIS) using methods previously described (SOZO Device, ImpediMed, Limited, Brisbane, Qld, Australia) [14]. This method has been shown to produce test-retest intraclass correlation coefficients (ICC) >0.990 for whole body fat mass, fat-free mass, and percent body fat in 29 men and women with comparable results to dual-energy X-ray absorptiometry in 95 men and women [14]. Additionally, the BIS method used has been identified as an acceptable alternative to dual-energy X-ray absorptiometry for use in clinical practice for body composition analyses [14].…”
Section: Body Composition and Hydration Testingmentioning
confidence: 99%
“…15,16 These devices are more convenient to use and are able to make measurements of all body segments simultaneously and save time by avoiding the need for the operator to move skin surface electrodes around the body and making repeat measurements. While these stand-on devices have been used extensively for body composition assessment [17][18][19][20] and to a limited extent for lymphedema assessment, 21 they have not been systematically assessed for comparability with conventional lead-type measurements. 22 van Zanten and Ward.…”
Section: Introductionmentioning
confidence: 99%
“…Thurlow et al and Esco et al reported that stand-on devices had several reported practical advantages, including permanently incorporated electrodes standardizing anatomical positioning and reduced total measurement time, all potential critical factors in obtaining accurate and precise measurements. 17,23 The aim of this study was to assess and compare BIS measurements made in three different body positions using two different impedance devices (lead device and stand-on device) in healthy women and those at risk of or living with arm lymphedema consequent to breast cancer treatment. Specifically, we plan to evaluate the following:…”
Section: Introductionmentioning
confidence: 99%
“…Tissue bioimpedance is related to the type of tissue, intra/extra cellular fluids, and overall tissue structure [3] . Bioimpedance measurements have been utilized for applications including: body composition determination [4] , [5] , clinical tomography [6] , cardiography [7] , respiratory monitoring [8] , and even food monitoring applications [9] . Bioimpedance is also currently being investigated as a noninvasive technique to characterize skeletal muscle tissue with a particular focus on assessing neuromuscular disorders [10] , [11] , [2] .…”
Section: Introductionmentioning
confidence: 99%